1987
DOI: 10.1104/pp.85.4.1008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mung Bean UDP-Glucose: (1→3)-β-Glucan Synthase by UDP-Pyridoxal

Abstract: UDP-pyridoxal competitively inhibits the Ca2`-, cellobiose-activated (1-.3)-#-glucan synthase activity of unfractionated mung bean (Vigna radiata) membranes, with a K, of 3.8 1 0.7 micromolar, when added simultaneously with the substrate UDP-glucose in brief (3 minute) assays. Preincubation of membranes with UDP-pyridoxal and no UDPglucose, however, causes progressive reduction of the V,., of subsequently assayed enzyme and, after equilibrium is reached, 50% inhibition occurs with 0.84 ± 0.05 micromolar UDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 8 publications
0
32
1
Order By: Relevance
“…A multitude of factors (Ca2", Mg2", proteases, nucleotides, phosphatases) have been identified as potential regulators of these enzymes (7,10,11,13,18,19). Purified enzymes would allow a new appraisal of the role of these factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of factors (Ca2", Mg2", proteases, nucleotides, phosphatases) have been identified as potential regulators of these enzymes (7,10,11,13,18,19). Purified enzymes would allow a new appraisal of the role of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…By using various techniques (gradient density centrifugation, column chromatography, electrophoresis) it has been shown that glucan synthases are large protein complexes (>450 kD), and several protein subunits ranging from 18 to 83 kD might be involved in glucan synthesis (5,16,19).…”
Section: Isolation Of Particulate Enzymesmentioning
confidence: 99%
“…[15][16][17][18] The molecular mass of the catalytic complex in plants has been further defined as having a molecular mass of 32-57 kDa by affinity labeling. [19][20][21][22][23] CalS combines to form a heteromeric complex with phragmoplastin, Ugt1, Rho1-like protein, and, possibly, annexin. [24][25][26] it appears that plant Rop1 controls CalS via UGT.…”
Section: Gsls In Monocotyledonous and Dicotyledonous Plantsmentioning
confidence: 99%
“…Read and Delmer (22) showed that the substrate analog UDP-pyridoxal, first used to identify the active site of glycogen synthase (25), is an effective inhibitor of callose synthase, apparently through formation of a Schiffs base with an active-site lysine; because inhibition was rendered irreversible after reduction of the Schiffs base with 'This work was supported by contract DE-ACO2- 76ERO-1338 from The U.S. Department of Energy via a subcontract from Michigan State University, East Lansing, MI, and by a grant from the German-Israeli Foundation for Scientific Research and Development (GIF). 2 Present address: Plant Cell Biology Research Centre, School of Botany, The University of Melbourne, Parkville, Vic.…”
mentioning
confidence: 99%
“…sodium borohydride, this analog offered the hope that the catalytic subunit might be identified by covalent coupling to the active site. There have been several reports of use of UDP-[3H]pyridoxal as labeled probe; in the first (22), a polypeptide of 42 kD from mung bean membranes was labeled, but labeling did not meet all the criteria expected for the catalytic subunit of callose synthase; a second report (19) indicated that a number of membrane proteins from red beet could be labeled; when the specificity of labeling was improved by a substrate protection technique, these were reduced to labeling ofpolypeptides of 200, 76, 60, and 57 kD. Wasserman's group also demonstrated the feasibility of using 5-azido-[32P]UDPglucose as an affinity labeling probe (16) and, in subsequent work using this probe (9), concluded that the 57 kD polypeptide of red beet is the most likely candidate for catalytic subunit of the enzyme based upon its enrichment upon product entrapment (see 13), its pH optimum for labeling, and its effector requirements.…”
mentioning
confidence: 99%